If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8p + 3c = -29 Reorder the terms: 3c + -8p = -29 Solving 3c + -8p = -29 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '8p' to each side of the equation. 3c + -8p + 8p = -29 + 8p Combine like terms: -8p + 8p = 0 3c + 0 = -29 + 8p 3c = -29 + 8p Divide each side by '3'. c = -9.666666667 + 2.666666667p Simplifying c = -9.666666667 + 2.666666667p
| 75=(-6x-5) | | x^2-18x+81=9 | | 8n^2+16n-280=0 | | 5=3(h-8)+8 | | 3t+17=11 | | -5(6x+6)=-300 | | 2(3+5)-5X= | | q-13=-50 | | 75+0.1x=200+0.05x | | 15-31=9z+24 | | 1,000=(10-5)x-5,000 | | -17g=-136 | | (-6-n+2n^2)+(8-3n-10n^2)= | | 12=24x-12 | | 3+12x=x | | 8x+7y=25 | | 4x+19-9x+8= | | 6y-4y+8+12a-15+2a= | | 8y-(4y+3)=21 | | x=1.5x^2-8x-.5*2 | | 2/3/2= | | m-34=15 | | -4=-(2w) | | 75-0.1x=400 | | 3-7+8y-3a-10y+15-a= | | (5x-3y)-(-5x-3y)= | | 8x-2=7x+4 | | 6y-9=21 | | 12=b+3 | | 0x=40 | | 6x-2x-3x= | | 4y-7(y+6)=5y+2 |